Development of method of testing a set of screen-exhaust devices in the helicopter Mi-8MSB-B - Kinaschuk, Mykhailo (Technology audit and production reserves, 2020)
The object of research is a set of screen-exhaust devices (SED) as part of the Mi-8MSB-V helicopter (Ukrainian version of the modernization of the Soviet multipurpose Mi-8 helicopter, developed by Motor Sich JSC, Zaporizhzhia, Ukraine). The SED set is designed to reduce the infrared signature of helicopters equipped with TV3-117 turboshaft engines of all modifications for the Mi-8MSB-V, Mi-8MT, Mi-14 and Mi-24. One of the problem areas is the lack of methods for solving the problem of determining the parameters and tactical and technical characteristics when examining SED as part of an aircraft during testing and research, which must be carried out in accordance with the approved Technical Operation Manual. When constructing the developed methodology, the rules of the Technical Operation Manual and the Helicopter Flight Operation Manual were applied, which allows testing in compliance with flight safety standards. Flight tests serve as a source of information for analytical calculations, the SED models and verification of their reliability by checking the convergence of the parameters of the functioning process under the same conditions using simulation and flight experiments. The developed technique of research and testing of a set of screen-exhaust devices makes it possible to check the performance of a specific sample in all flight modes. The technique makes it possible to determine the level of engine power losses in different operating modes using the parameters of the on-board information collection facilities in conjunction with SED. This makes it possible to obtain a characteristic of fuel consumption in the case of a set of screen-exhaust devices installed on board and without it. The technique takes into account the possibility of simultaneously conducting both flight and ground tests of SED to construct an infrared radiation indicatrix and determine the distances and angles of target capture by the homing head of portable anti-aircraft missile systems. Analysis of the data obtained made it possible to determine the direction of further computational and experimental studies aimed at improving the flow path of the SED.